Association of hemoglobin, albumin, lymphocyte, and platelet score with risk of cerebrovascular, cardiovascular, and all-cause mortality in the general population: results from the NHANES 1999-2018 - Pan, Hong; Lin, Shasha (Frontiers in Endocrinology, 2023)
Background and Aims: Cardiovascular and cerebrovascular disease (CCDs) contribute to leading causes of morbidity and mortality in the United States of America (USA). Hemoglobin, albumin, lymphocyte, and platelet (HALP) score, a simple and convenient indicator, could reflect the combination of inflammation and nutritional status. This study was undertaken to evaluate the associations between HALP score and risk of cardiovascular, cerebrovascular, and all-cause mortality in the general population from the National Health and Nutrition Examination Survey (NHANES) 1999–2018. Methods: We identified 21,578 participants during the 1999-2018 cycles of the NHANES in this research. HALP score was calculated as hemoglobin (g/L) × albumin (g/L) × lymphocytes (/L) / platelets (/L). Outcomes were cerebrovascular, cardiovascular, and all-cause mortality determined by the NHANES-linked National Death Index record and followed until 31 December 2019. Survey-weighted Cox regression, restricted cubic spline analysis, and subgroup analysis were applied to investigate relationships between HALP score and risk of mortality. Results: This cohort study comprised 49.2% male and 50.8% female, of which the median age was 47 years old. In multivariate survey-weighted Cox regression adjusting for all confounders, compared with participants with low HALP scores, participants with highest HALP score had a lower risk of all-cause mortality (adjusted HR:0.80, 95% CI: 0.73, 0.89, P < 0.0001) and cardiovascular mortality (adjusted HR:0.61, 95% CI: 0.50, 0.75, P < 0.0001), and mediate HALP score had the lowest risk of all-cause mortality (adjusted HR:0.68, 95% CI: 0.62, 0.75, P < 0.0001) and cardiovascular mortality (adjusted HR:0.60, 95% CI: 0.48, 0.75, P < 0.0001). Restricted cubic spline analysis showed a non-linear relationship between HALP score and cardiovascular and all-cause mortality (all P values <0.001). Conclusions: HALP score was independently associated with risk of cardiovascular and all-cause mortality, but not cerebrovascular mortality.